Implementation of Educational Management through Joyful Learning to Shape Grade 2 Students' Discipline Character - Amalia, Sofia; Nisa, Choirun (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to analyze the implementation of educational management through the Joyful Learning approach in shaping the disciplinary character of second-grade students at SD Negeri 01 Karang. The research focuses on how management functions planning, organizing, actuating, and controlling are applied to support structured, engaging, and character-oriented learning.Methodology: This study employs a qualitative descriptive approach. Data were collected through classroom observations, in-depth interviews with teachers, students, and parents, as well as documentation of learning activities and school records. The data were analyzed through data reduction, data display, and conclusion drawing to obtain a comprehensive understanding of learning processes and discipline formation.Results: The findings show that educational management plays a significant role in strengthening student discipline. Teachers collaborate with students in setting classroom rules, organize student roles systematically, model positive behavior, and conduct continuous monitoring. Joyful Learning, implemented through educational games, songs, visual media, and group activities successfully increases students’ motivation, focus, and engagement. The enjoyable learning atmosphere enables students to follow instructions, behave more orderly, and complete tasks on time. Supporting factors include teacher creativity, school leadership support, and parental involvement, while inhibiting factors consist of limited media, varied student characteristics, and time constraints.Applications/Originality/Value: This study provides both theoretical and practical insights into the integration of educational management and Joyful Learning as an effective strategy for developing disciplinary character in elementary students. The findings serve as a model for teachers in designing learning activities that are simultaneously joyful and characterbuilding.